Algoritma Heuristik untuk Menentukan Biaya Crashing Minimum pada Project Network dengan Dua Jalur Kritis: Studi Kasus Proyek Produksi Electrical House oleh PT X - Berry Yuliandra; Rini Syahfitri (Jurnal Optimasi Sistem Industri, 2015)
PT X is a company engaged in the production of the module, ship relay station (Electrical House)as well as oil and gas mining equipment. The company uses a project-based production system in the production process of that equipment. Type of project usually performed is the Engineering-Procurement-Construction (EPC) project. EPC is a type of project that involves process engineering, material procurement, and products construction. PT X main product is a module or electrical house (E-House). Activities can be disrupted by a variety of conditions in the project implementation phase, such as weather and other unforeseen events. These conditions can hamper the process and affect the performance on the field.Activity scheduling and load out process which often suffer from delays caused project deadlines are often past the limit is given by the client. As in the case of E-House project examined in this study, its implementation has been delayed and should be accelerated for 8days. Therefore, the crashing project can greatly assist in adjusting the implementation plan with the actual condition. Crashing project analysis conducted based on project network diagram. The critical path is determined using Critical Path Method (CPM). Based on analysis results, project execution time can be shortened up to 8 days earlier. (From the normal time of 94 days to 86 days) at the cost $ 4.203.093,25.